Six‐Month Assessment of a Hand Prosthesis with Intraneural Tactile Feedback. Issue 1 (24th December 2018) - Petrini, Francesco M.; Valle, Giacomo; Strauss, Ivo; Granata, Giuseppe; Di Iorio, Riccardo; D'Anna, Edoardo; Čvančara, Paul; Mueller, Matthias; Carpaneto, Jacopo; Clemente, Francesco; Controzzi, Marco; Bisoni, Lorenzo; et al.
Abstract : Objective: Hand amputation is a highly disabling event, which significantly affects quality of life. An effective hand replacement can be achieved if the user, in addition to motor functions, is provided with the sensations that are naturally perceived while grasping and moving. Intraneural peripheral electrodes have shown promising results toward the restoration of the sense of touch. However, the long‐term usability and clinical relevance of intraneural sensory feedback have not yet been clearly demonstrated. Methods: To this aim, we performed a 6‐month clinical study with 3 transradial amputees who received implants of transverse intrafascicular multichannel electrodes (TIMEs) in their median and ulnar nerves. After calibration, electrical stimulation was delivered through the TIMEs connected to artificial sensors in the digits of a prosthesis to generate sensory feedback, which was then used by the subjects while performing different grasping tasks. Results: All subjects, notwithstanding their important clinical differences, reported stimulation‐induced sensations from the phantom hand for the whole duration of the trial. They also successfully integrated the sensory feedback into their motor control strategies while performing experimental tests simulating tasks of real life (with and without the support of vision). Finally, they reported a decrement of their phantom limb pain and a general improvement in mood state. Interpretation: The promising results achieved with all subjects show the feasibility of the use of intraneural stimulation in clinical settings.ANN NEUROL 2019;85:137–154.